Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan bagian Supply Chain Management PT. ABC di Bandung - Julistia, Thasyanandya; Mochamad Vrans Romi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of work motivation and work discipline on employee performance in the Supply Chain Management department of PT. ABC in Bandung, both partially and simultaneously. The research method used was quantitative descriptive and associative, using a survey approach using questionnaires, interviews, and documentation with 35 employees as respondents using a saturated sampling technique. The results showed that work motivation and work discipline were in the high category, and employee performance was classified as very good. Based on multiple linear regression analysis, work motivation and work discipline had a positive and significant effect on employee performance, both partially and simultaneously, with a contribution of 76.8%. The conclusion of this study is that the higher the employee motivation and work discipline, the higher the performance in the Supply Chain Management department of PT. ABC Bandung.   Keywords: Work Motivation, Work Discipline, Employee Performance, Supply Chain